Metallicity estimates of young clusters in the Magellanic Clouds from Strömgren photometry of supergiant stars - Piatti, Andres Eduardo (2019)
We present results obtained from Stromgren photometry of 13 young (~ 30-220 Myr) Magellanic Cloud (MC) clusters, most of them lacking in the literature from direct metallicity measurements. We derived for them [Fe/H] values from a high-dispersion spectroscopy-based empirical calibration of the Stromgren metallicity sensitive index m1 for yellow and red supergiants (SGs).  Particular care was given while estimating their respective uncertainties. In order toobtain the mean cluster metallicities, we used [Fe/H] values of selected SGs for which we required to be located within the cluster radii, placed in the expected SG region in the clustercolour-magnitude diagrams, and with [Fe/H] values within the FWHM of the observed cluster metallicitydistributions. The resulting metallicities for nearly 75 per cent of the cluster sample agree well with the most frequently used values of the mean MCs´ present-day metallicities.The remaining clusters have mean [Fe/H] values that fall near the edge of the MC present-daymetallicity distributions.  When comparing the cluster metallicities with their present positions, we found evidence that supports the claimed recent interaction of the MCs with the Milky Way, that could have caused that some clusters were scattered from their birthplaces. Indeed, we show examples of clusters with metal contents typical of the galaxy innerregions placed outward them. Like wise, we found young clusters, at present located in the inner regions of both MCs, formed out of gas that has remained unmixed since several Gyr ago.